Coexistence of LMPP-like and GMP-like Leukemia Stem Cells in Acute Myeloid Leukemia - Goardon, Nicolas; Marchi, Emanuele; Atzberger, Ann; Quek, Lynn; Schuh, Anna; Soneji, Shamit; Woll, Petter; Mead, Adam; Alford, Kate A.; Rout, Raj; Chaudhury, Salma; Gilkes, Amanda; et al. (Cancer cell, 2011)
The relationships between normal and leukemic stem/progenitor cells are unclear. We show that in ∼80% of primary human CD34+ acute myeloid leukemia (AML), two expanded populations with hemopoietic progenitor immunophenotype coexist in most patients. Both populations have leukemic stem cell (LSC) activity and are hierarchically ordered; one LSC population gives rise to the other. Global gene expression profiling shows the LSC populations are molecularly distinct and resemble normal progenitors but not stem cells. The more mature LSC population most closely mirrors normal granulocyte-macrophage progenitors (GMP) and the immature LSC population a previously uncharacterized progenitor functionally similar to lymphoid-primed multipotential progenitors (LMPPs). This suggests that in most cases primary CD34+ AML is a progenitor disease where LSCs acquire abnormal self-renewal potential. [Display omitted] ► Most human CD34+ AMLs have two molecularly distinct LSC populations ► They are hierarchically ordered in vivo and in vitro ► Molecularly, LSCs are most similar to normal progenitors rather than stem cells ► The more immature LSCs most closely mirror normal LMPPs